First record of Microscapha LeConte from Baltic amber with description of a new species and list of fossil Melandryidae (Coleoptera: Tenebrionoidea) - Bukejs, Andris; Alekseev, Vitalii I. (Zootaxa, 2015)
Microscapha andrzeji sp. nov., the first fossil representative of the genus is described from Eocene Baltic amber. An updated list of fossil Melandryidae (Coleoptera: Tenebrionoidea) is provided. The presence of Microscapha within Baltic amber suggests some potential for palaeoenvironmental inferences based on the melandryid assemblage within the deposit.